Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches. (1st August 2012) - Sheik, A. R.; Brussaard, C. P. D.; Lavik, G.; Foster, R. A.; Musat, N.; Adam, B.; Kuypers, M. M. M.
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l−1). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l−1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.